Investigating the biological significance of the TCM principle “promoting urination to regulate bowel movements” through the influence of the intestinal microbiota and their metabolites on the renal-intestinal axis - Yu, Donglin; Shen, Junxi; Li, Liwen; Long, Qi; Xie, Shiqin; Zhou, Mengsi; Tian, Qianghong; Cai, Ying (Frontiers in Cellular and Infection Microbiology, 2025)
Treatment methods in traditional Chinese medicine (TCM) are foundational to their theoretical, methodological, formulaic, and pharmacological systems, significantly contributing to syndrome differentiation and therapy. The principle of “promoting urination to regulate bowel movements” is a common therapeutic approach in TCM. The core concept is “promoting the dispersion and drainage of water dampness, regulating urination to relieve diarrhea,” yet its scientific underpinning remains unclear. Modern medical treatment for watery diarrhea primarily focuses on electrolyte replenishment, as diuretics may lead to dehydration and other side effects. Some reports suggest that this TCM approach lacks scientific validity. Microecology, an area associated with the origins of TCM, is closely related to the development, diagnosis, and treatment of diarrhea. The renal-intestinal axis offers a molecular biological basis for examining associated pathological mechanisms, advancing therapeutic targets such as “treating the intestine to address kidney issues” and highlighting the interactions within the “renal-intestinal microbiota-liquid metabolism” framework, thus providing an endogenous mechanism to support “treating the intestine through the kidney.” An increasing number of studies have shown that the intestinal microbiota and its metabolites, as unique mediators, are involved in the physiological and pathological changes of the body. Therefore, this study explores the relationship between fluid metabolism and diarrhea from the perspective of the intestinal microbiota and its metabolites, aiming to elucidate the biological mechanisms underlying the “promoting urination to regulate bowel movements” therapeutic approach and to clarify the scientific basis for treating diarrhea via the renal-intestinal axis. This research provides new insights for the study of TCM microbiology.